Determination of the promoter strength of the gene encoding Escherichia coli heat-stable enterotoxin II. - Spandau, D F (1987)
We studied the promoter strength of the gene encoding the Escherichia coli heat-stable enterotoxin II (STII). The promoter region and a portion of the 5' coding sequence of the STII gene were fused to the lacZ gene so that the production of beta-galactosidase was under the control of the STII gene promoter. The strength of the STII gene promoter was compared with that of the ompF and lac operons, which were similarly fused to the lacZ gene. The beta-galactosidase produced by the hybrid genes was assayed in vitro by using cell extracts. The mRNA transcribed by each promoter was assayed by Northern blot analysis and by in vitro transcription. The results suggest that the STII gene is regulated by a relatively weak promoter.